2018
DOI: 10.1111/jsr.12741
|View full text |Cite
|
Sign up to set email alerts
|

Are serum ferritin and transferrin saturation risk markers for restless legs syndrome in young adults? Longitudinal and cross‐sectional data from the Western Australian Pregnancy Cohort (Raine) Study

Abstract: Restless legs syndrome has been associated with serum iron deficiency in clinical studies. However, studies investigating this relationship have had inconsistent results and there are no studies in young adults. Therefore, we investigated the relationship between serum measures of iron stores and restless legs syndrome in young adults in the community. Participants in the Western Australian Pregnancy Cohort (Raine) Study answered questions on restless legs syndrome (n = 1,100, 54% female) at age 22 years, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…Despite the absence of standardized cut-offs for serum hepcidin levels, high serum hepcidin levels (≥ 20.99 ng/mL) were associated with older age, older age at RLS onset, positive family history of RLS, lower excessive daytime sleepiness; however these results should be taken with caution regarding the multiple testing performed and the sample size of the population. The best hepcidin cut Although serum ferritin is considered as the most informative RLS biomarker, in our study ferritin level was not different between patients with RLS and controls, as previously reported [9][10][11][12][13] . Moreover, the percentage of subjects with ferritin level < 50 ng/mL was similar in the RLS and control groups.…”
Section: Discussionsupporting
confidence: 72%
“…Despite the absence of standardized cut-offs for serum hepcidin levels, high serum hepcidin levels (≥ 20.99 ng/mL) were associated with older age, older age at RLS onset, positive family history of RLS, lower excessive daytime sleepiness; however these results should be taken with caution regarding the multiple testing performed and the sample size of the population. The best hepcidin cut Although serum ferritin is considered as the most informative RLS biomarker, in our study ferritin level was not different between patients with RLS and controls, as previously reported [9][10][11][12][13] . Moreover, the percentage of subjects with ferritin level < 50 ng/mL was similar in the RLS and control groups.…”
Section: Discussionsupporting
confidence: 72%
“…Currently, serum ferritin is used to guide treatment, but we have discussed the concerns regarding the utility of serum ferritin both as a measure of total body iron stores and serum ferritin levels are of no value in predicting response to treatment. Lammers et al studied serum ferritin, bodily iron, and RLS, finding no association between early-onset RLS and longitudinal measures of iron stores [136]. Similarly, while serum ferritin is currently used clinically to guide treatment, it has been shown that serum ferritin levels have no predictive value in the response to treatment [131].…”
Section: Ferritin As a Disease Biomarkermentioning
confidence: 99%
“…[ 22 ] It is not clear whether RLS is related to low iron levels in the peripheral or central nervous system (CNS). Early evidence suggests that the severity of RLS increases with a decrease in peripheral iron, which may be related to the level of peripheral iron [ 23 ] and that the morbidity of RLS is higher in patients with peripheral iron deficiency. [ 24 ] However, recent findings have challenged these findings, with a population-based study establishing that RLS is not associated with plasma ferritin levels.…”
Section: Pathophysiologymentioning
confidence: 99%